Towards Identification & Evaluation of Training Needs - Ghatak, Rangana; Singh, Namrata (SFIMAR Research Review, 2011)
The main purpose of this paper is to Identify and analyze the Functional and Behavioral Training Needs. For this purpose data was collected from Rashtriya Chemicals & Fertilizers Ltd (RCF). Data was collected from both primary as well secondary sources. For the purpose of analysis, the data is divided into 3 levels of Management; Senior, Middle & Junior. The data is then analyzed on the basis of training needs. At the end of the report are the inferences from the analysis and suggestions.